Rare desmoplastic myxoid tumor of pineal region, SMARCB1 mutant in adult - A brief report - Moothedath, Rajesh Menon; V R, Roopesh Kumar; Lalgudi Srinivasan, Harishchandra; Patil, Shushma; Raju, Saranyan; R, Babu (Journal of Neurosurgery Academy, 2025)
A 40-year-old lady presented with clinical features of Parinaud syndrome. Contrast MRI showed a mass in the pineal region with tectal compression and moderate obstructive hydrocephalus. She underwent gross total excision of the lesion through an occipital transtentorial approach. Histopathology and IHC were confirmative of desmoplastic myxoid tumor (DMT), a SWI/SNF-related matrix-associated actin-dependent regulator of chromatin subfamily B member 1 (SMARCB1) mutant of the pineal region predominantly seen in adolescents and older individuals with a slight preponderance to females (M:F, 4:6). SMARCB1 mutant DMT is a recently described yet sporadic and distinct pineal parenchymal tumor according to the new WHO 2021 classification. Even though the tumor has a better prognosis as per limited literature reviews, its optimum therapeutic protocol is evolving. The neoplasm is characterized by alterations of the SMARCB1/INI1 locus with variable amounts of desmoplasia and myxoid matrix. We hope this case study will provide additional insight into this newly described neoplastic entity and its management.